Allergic reaction to acrylic resin in a patient with a provisional crown: case report - Alfredo Mikail Melo Mesquita; Juliano H M Silva; Alberto Noryuki Kojima; Renata Vasconcelos Moura; Elcio Madaglena Giovani; Mutlu Özcan (Brazilian Dental Science)
Acrylic resins are widely used in dentistry, especially in orthodontics and prosthetics. Patients: this article reports the case of a leukodermic 33-year-old male who reported discomfort and pain due to an erythematous lesion in the first left premolar after the placement of an acrylic resin temporary restoration. Discussion: The signs and symptoms presented by the patient and his report of visiting the rural countryside generated concern regarding the possible diagnosis, which led to a more invasive biopsy to differentiate allergic inflammation from a paracococcidioid mycosisIncisional. Biopsy revealed a chronic inflammatory process. Conclusion: the pathology was caused by contact with methyl methacrylate-based provisional acrylic resin.